PENALARAN MATEMATIS MAHASISWA DALAM MENYELESAIKAN MASALAH MATEMATIKA DITINJAU DARI PSIKOLOGI KOGNITIF: SEBUAH SYSTEMATIC LITERATURE REVIEW - Randi Pratama Murtikusuma; Susanto Susanto; Abi Suwito (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to systematically review preservice teacher mathematical reasoning in solving mathematical problems from a cognitive psychology perspective. A systematic literature review was conducted on indexed journal articles published between 2020 and 2025, resulting in about forty studies relevant to mathematical reasoning, problem solving, proof, and cognitive and affective factors among university students or pre service teachers. Articles were collected from international and national databases using combinations of mathematical reasoning, university students, cognitive psychology, metacognition, beliefs, and habits of mind and then selected through identification, screening, and eligibility stages. The synthesis indicates that students’ mathematical reasoning is generally at a moderate level with weaknesses in generalization and formal proof, while procedural manipulation tends to be stronger. Working memory, metacognition, thinking dispositions, and positive beliefs about mathematics positively correlate with reasoning quality, whereas anxiety and negative beliefs hinder students’ willingness to argue and explore non routine strategies. Several instructional models such as problem based, realistic, cooperative, and reflection oriented learning supported by metacognitive scaffolding are consistently reported to improve mathematical reasoning. This review highlights the need to integrate high level mathematical task design with deliberate management of students' cognitive and affective characteristics in university mathematics education. ABSTRAK Penelitian ini mengkaji secara sistematis penalaran matematis mahasiswa dalam menyelesaikan masalah matematika melalui perspektif psikologi kognitif. Melalui systematic literature review terhadap artikel terindeks tahun 2020–2025, teridentifikasi sekitar empat puluh studi yang membahas penalaran, pemecahan masalah, pembuktian, serta faktor kognitif dan afektif pada mahasiswa atau calon guru. Pencarian dilakukan pada basis data internasional dan nasional menggunakan kombinasi kata kunci mathematical reasoning, university students, cognitive psychology, metacognition, beliefs, dan habits of mind, kemudian diseleksi melalui tahap identifikasi, penyaringan, dan kelayakan. Sintesis temuan menunjukkan bahwa penalaran matematis mahasiswa umumnya berada pada kategori sedang dengan kelemahan terutama pada kemampuan generalisasi dan penyusunan bukti formal, sedangkan kekuatan lebih tampak pada manipulasi prosedural. Faktor seperti memori kerja, metakognisi, disposisi berpikir, dan keyakinan positif terhadap matematika berkontribusi pada kualitas penalaran, sementara kecemasan dan keyakinan negatif cenderung menghambat keterlibatan dan keberanian berargumentasi. Berbagai model pembelajaran berbasis masalah, realistik, kooperatif, dan reflektif yang dipadukan dengan dukungan metakognitif konsisten dilaporkan mampu meningkatkan penalaran matematis. Kajian ini menegaskan perlunya integrasi antara desain tugas matematika tingkat tinggi dan pengelolaan aspek psikologi kognitif mahasiswa dalam pembelajaran di perguruan tinggi.